Vascular Dysfunction in Malaria: Understanding the Role of the Endothelial Glycocalyx - Bush, Margaret A.; Anstey, Nicholas M.; Yeo, Tsin W.; Florence, Salvatore M.; Granger, Donald L.; Mwaikambo, Esther D.; Weinberg, J. Brice (Frontiers in Cell and Developmental Biology, 2021)
Malaria caused by Plasmodium falciparum results in over 400,000 deaths annually, predominantly affecting African children. In addition, non-falciparum species including vivax and knowlesi cause significant morbidity and mortality. Vascular dysfunction is a key feature in malaria pathogenesis leading to impaired blood perfusion, vascular obstruction, and tissue hypoxia. Contributing factors include adhesion of infected RBC to endothelium, endothelial activation, and reduced nitric oxide formation. Endothelial glycocalyx (eGC) protects the vasculature by maintaining vessel integrity and regulating cellular adhesion and nitric oxide signaling pathways. Breakdown of eGC is known to occur in infectious diseases such as bacterial sepsis and dengue and is associated with adverse outcomes. Emerging studies using biochemical markers and in vivo imaging suggest that eGC breakdown occurs during Plasmodium infection and is associated with markers of malaria disease severity, endothelial activation, and vascular function. In this review, we describe characteristics of eGC breakdown in malaria and discuss how these relate to vascular dysfunction and adverse outcomes. Further understanding of this process may lead to adjunctive therapy to preserve or restore damaged eGC and reduce microvascular dysfunction and the morbidity/mortality of malaria.